“From Scenic Interpretation to Fluent Speaking: Literary Texts “Linie 1” in the German Classroom” - Cansrina, Genita; Gantrisia, Kamelia; Ratnasari, Dewi (Nusantara Science and Technology Proceedings)
These article explores the question of how literary texts can be didactizised in foreign language classroom. Based on the hypothesis that the students are still shy and reserved despite the sufficient knowledge of German, the main goal of this research ist an attempt to make the learners speak. Scenic interpretation, whose term originated from the scenic play, was concepted by Scheller (1996) in order to give literature back its meaning when he noticed the students showed a distance to foreign literary texts. This method connected the theater pedagogy with the teaching of German as a foreign language, in which two central orientations can be distinguished, namely process orientation and product orientation. In the field of foreign language acquisition, this method serves to improve oral communication skills and thus a process-oriented orientation is pursued. If one considers scenic interpretation as a methodological approach in German teaching, teaching with the means of theater is part of an action-oriented teaching, in which the students are in the center, because they themselves are active and the teacher gets more the tasks as an organizer of the learning process. The selected corpus of this research ist “Linie 1”, a musical revue by Ludwig (2007), in which Berlin dialect can be often be heard as one of the signs of authentic conversation in the scenes of subway. Not only from hearing, but also from seeing, learners get input from this musical performance, through which it is assumed that it is easier for them to imagine the spaces, the situation, the relationship and the images to interpret the texts. In order to make the students aware of the contrastive considerations, questionnaires are distributed to them, in which a few questions are asked according to the learner´s sensations. Furthermore, these literary texts are didactizised using the Four Strands model developed by Paul Nation (2007). The preliminary result of this research can be said, that after one semester sessions, the students speak more fluently because they are familiarized with the text and therefore they have more self-confidence.